Diversity of genus Psathyrella (Psathyrellaceae, Agaricales) from Punjab, India - KAUR, HARWINDER (Mushroom Research, 2020)
A detailed investigation of species of Psathyrella was carried out in Punjab State, India. In this paper, 17 collections belonging to 14 species of genus Psathyrella has been worked out for their external, internal details & key to identification for these species has been given. These species include P. patialensis sp. nov., P. aurantiacoumbonata sp. nov., P. plicatilis sp. nov., P. incerta, P. moshiana, P. singeri, P. dichroma, P. barrowsii, P. murrillii, P. candolleana var. solitaria, P. araguana, P. candolleana, P. longistriata & P. floccosa. Out of these, three species proposed as new species viz. P. patialensis sp. nov., P. aurantiacoumbonata sp. nov., & P. plicatilis sp. nov. For all these species, detailed description of all the macroscopic & microscopic characters and of line drawings with the help of Camera Lucida are given. The taxonomy of three taxa is discussed along with the drawings of morphological & anatomical features.